Foreigners and outside influences in medieval Norway - Suppersberger Hamre, Stian (Archaeopress Publishing Ltd, 2017)
Seven articles discuss different aspects of immigration and foreign influences in medieval Norway, from the viewpoint of different academic disciplines. The book will give the reader an insight into how the population of medieval Norway interacted with the surrounding world, how and by whom it was influenced, and how the population was composed.